2007
DOI: 10.1007/s11104-007-9322-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heavy metal pollution on genetic diversity in zinc/cadmium hyperaccumulator Sedum alfredii populations

Abstract: The genetic diversity and population structure of seven populations of Sedum alfredii growing in lead/zinc (Pb/Zn) mine spoils or in uncontaminated soils from eastern and southern China were investigated using random amplified polymorphic DNA (RAPD) technology. Four of the sampled sites were heavily contaminated with heavy metals (Zn, Cd, Pb), and extremely high concentrations of Zn, Cd, and Pb were found among these corresponding populations. A significant reduction of genetic diversity was detected in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 40 publications
5
36
2
1
Order By: Relevance
“…Copper was chosen because previous chemical analysis revealed that it is present in elevated amounts (over one order of magnitude) in a historically contaminated area relatively to other nearby sites. Genetic diversity was estimated by random amplified polymorphic DNA (RAPD) [13]; RAPD markers have been used in several ecotoxicological studies [14,15] to assess the effects of anthropogenic contaminants on population genetic diversity. This method does not require previous DNA sequence information and so is adequate when few genetic data are available, such as for the terrestrial isopod P. sexfasciatus.…”
Section: Introductionmentioning
confidence: 99%
“…Copper was chosen because previous chemical analysis revealed that it is present in elevated amounts (over one order of magnitude) in a historically contaminated area relatively to other nearby sites. Genetic diversity was estimated by random amplified polymorphic DNA (RAPD) [13]; RAPD markers have been used in several ecotoxicological studies [14,15] to assess the effects of anthropogenic contaminants on population genetic diversity. This method does not require previous DNA sequence information and so is adequate when few genetic data are available, such as for the terrestrial isopod P. sexfasciatus.…”
Section: Introductionmentioning
confidence: 99%
“…Although both these sites have been able to recover to some extent over the past 30 years due to emission reductions and remediation efforts (Dudka et al, 1995;Nkongolo et al, 2008), fact remains that such highly contaminated mine tailings often have metal concentrations that are increased to a level that are toxic for the majority of plants (Jiménez-Ambriz et al, 2007). The toxic metal pollutants, accompanied by the detrimental physical disturbances in the environment can influence plant survivorship, recruitment, reproductive success, mutation rates and migration, all of which affect the genetic diversity of the exposed populations (Deng et al, 2007). To date, hundreds of metal-tolerant genotypes have been identified from a wide variety of plant species surviving on such metal contaminated soils with many different life stories, pollinating systems and life-spans at an unexpectedly high rate (Mengoni et al, 2000;Wu et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…To date, hundreds of metal-tolerant genotypes have been identified from a wide variety of plant species surviving on such metal contaminated soils with many different life stories, pollinating systems and life-spans at an unexpectedly high rate (Mengoni et al, 2000;Wu et al, 1975). This type of rapid and widespread adaptation to metal pollution suggests that the evolution of metal tolerance is one of the major strategies for plant colonization of mining spoils (Deng et al, 2007). Several investigations on the genetic diversity among metal tolerant populations relative to their non-metal tolerant counterparts have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a population can inadvertently eliminate other alleles from its gene pool. This loss of diversity can reduce its adaptation potential in the future (Mejnartowicz, 1983;Mengoni et al, 2001;Deng et al, 2007;Gervais and Nkongolo, 2011). It is therefore important to monitor the dynamics of genetic variability within and among plant populations.…”
Section: Introductionmentioning
confidence: 99%